2021
DOI: 10.1007/s10639-021-10725-7
|View full text |Cite
|
Sign up to set email alerts
|

Web-based discussions in teaching and learning: Secondary school teachers’ and students’ perception and potentiality to enhance students’ performance in organic chemistry

Abstract: The current work explores the secondary school teachers’ and students’ perception on web-based discussions in teaching and learning and its potentiality to enhance students’ performance in organic chemistry. A mixed approaches typically interviews and achievement tests were applied for collecting qualitative and quantitative data respectively for triangulation purpose. A total of 138 senior five students and 4 teachers were purposively selected from the two secondary schools at Kicukiro District in Kigali city… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…Cigdemoglu and Geban (2015) revealed that supporting conceptual understanding is challenging, and while integrating the 5E model, students improved their understanding of chemical reactions. Likewise, webbased discussion (Iyamuremye et al, 2021) and web-based simulation (Olakanmi, 2015) accelerated students' understanding of chemical reactions.…”
Section: Discussionmentioning
confidence: 99%
“…Cigdemoglu and Geban (2015) revealed that supporting conceptual understanding is challenging, and while integrating the 5E model, students improved their understanding of chemical reactions. Likewise, webbased discussion (Iyamuremye et al, 2021) and web-based simulation (Olakanmi, 2015) accelerated students' understanding of chemical reactions.…”
Section: Discussionmentioning
confidence: 99%
“…Occupational therapy uses specific activities to assist in the recovery of various physical or psycho-psychological disorders and alleviate and soothe students' developmental or social dysfunctions to achieve maximum independence in life [ 8 ]. This paper explores the sense of organic integration of labor education and occupational therapy for college students, which can help them adapt to social functioning, increase their confidence in facing environmental challenges, enhance their social adjustment, strengthen their self-identity, and promote the normalization of social life [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Further, this is supported by different research findings with an emphasis that any approach is effective when it responds to students’ needs. The study conducted by (Iyamuremye et al, 2021 ) on one hundred thirty-eight senior five chemistry students and four chemistry teachers from the two secondary schools at Kicukiro District in Kigali city, Rwanda about the effectiveness of web-based discussion in teaching and learning organic chemistry. It revealed that web-based discussion is a potential and effective tool that increases student performance.…”
Section: A Critical Reflection On Wbl In Teaching and Learning Chemis...mentioning
confidence: 99%